The “wall of text” visual structure of academic conference posters - Faulkes, Zen (Frontiers in Communication, 2023)
Posters created for conferences are a type of visual communication that is used almost exclusively by academics, and they may have properties of both documents and graphic displays. There are rarely any formatting requirements beyond fitting on their provided boards. But conference posters are often highly similar, despite the lack formal constraints from conference organizers. To test whether the visual structure of conference posters is influenced by journal articles, award-winning student posters from a large scientific society were examined. About three-quarters use the “Introduction, methods, results, discussion” format common to journal articles; about two-thirds use a columnar layout; most show multiple graphs and cite multiple references.